“Age of risk” shapes simpler multimodal communication in the juvenile plains zebra (Equus quagga) - Severine B. S. W. Hex; Daniel I. Rubenstein (Communications Biology)
Abstract Juveniles occupy a different social niche than adults, engaging in a smaller diversity of social contexts and perceiving greater social risks. Either or both of these factors may influence the form communication takes in immaturity and its developmental trajectory. We investigated the relative influence of these social forces on the development of multimodal communication in plains zebras (Equus quagga). Juveniles possessed smaller repertoires than adults, with lower combinatorial flexibility and greater stereotypy, particularly for signals used in submission. When interacting with adults, juveniles used a larger fraction of their repertoire, but with reduced combinatorial flexibility. The usage of a contextually flexible signal, “snapping”, also shifted across development, beginning as a stereotyped, submissive signal before diversifying into the full range of adult usage. Taken together, the lower complexity of juvenile communication may reduce signal ambiguity and the risk of miscommunication when interacting with social partners perceived as higher risk, like adults.